PENGEMBANGAN PUSAT STUDI PENELITIAN PRODUK HALAL BERBASIS PENGUJIAN SAINTIFIK [STUDI KASUS PENGUJIAN PRODUK HALAL PADA MAKANAN MENGGUNAKAN INSTRUMEN GC/MS, FTIR, PCR DAN ELECTRONIC NOSE] - Fajar Hardoyono (Jurnal Penelitian Agama, 2015)
Abstract: This article discusses the testing of food products processed meat using real time PCR instrument, an infrared spectrophotometer FTIR, GCMS, and electronic nose. Samples tested were processed meat products that include pure beef, mutton pure, pure pork, beef sausage, chicken sausage, goat sausage, pork sausage, veal nuggets, chicken nuggets, as well as processed products deliberately contaminated with the pigs. Testing of samples using four types of instruments that includes real-time PCR, spectrophotometry infrared FTIR, GC/MS, and the electronic nose was able to distinguish good quantitative differences between one sample with another sample. In the sample testing of food products manufactured by large-scale manufacturer of Small and Medium Enterprises (SMEs) and have not labeled halal, researchers have not found contamination pork elements on sausages nuggets, beef, and meatballs products. Keywords: Authentication Halal, Real Time PCR, FTIR, GC/MS, E-nose, Meat